PH-dependent Activities and Structural Stability of Loop-2-anchoring Helix of RadA Recombinase from Methanococcus voltae - D. E. C. S, Rao (Bentham Science Publishers, 2014)
RadA is an archaeal orthologue of human recombinase Rad51. This superfamily of recombinases, which also includes eukaryal meiosis-specific DMC1 and remotely related bacterial RecA, form filaments on single-stranded DNA in the presence of ATP and promote a strand exchange reaction between the single-stranded DNA and a homologous double-stranded DNA. Due to its feasibility of getting crystals and similarity (> 40% sequence identity) to eukaryal homologues, we have studied RadA from Methanococcus voltae (MvRadA) as a structural model for understanding the molecular mechanism of homologous strand exchange. Here we show this protein’s ATPase and strand exchange activities are minimal at pH 6.0. Interestingly, MvRadA’s pH dependence is similar to the properties of human Rad51 but dissimilar to that of the well-studied E. coli RecA. A structure subsequently determined at pH 6.0 reveals features indicative of an ATPase-inactive form with a disordered L2 loop. Comparison with a previously determined ATPase-active form at pH 7.5 implies that the stability of the ATPase-active conformation is reduced at the acidic pH. We interpret these results as further suggesting an ordered disposition of the DNA-binding L2 region, similar to what has been observed in the previously observed ATPase-active conformation, is required for promoting hydrolysis of ATP and strand exchange between single- and double-stranded DNA. His-276 in the mobile L2 region was observed to be partially responsible for the pH-dependent activities of MvRadA.